(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Women’s cooperative banks have emerged as crucial instruments for fostering economic empowerment among women, particularly in rural and semi-urban regions. These banks, managed and operated largely by women, provide a supportive financial ecosystem tailored to the unique needs of female clients. This review explores the role of women’s cooperative banks in facilitating financial inclusion, promoting entrepreneurship, improving saving habits, and enhancing women’s decision-making capacities. The article also discusses the challenges faced by these banks and offers policy recommendations for strengthening their impact.